Approach to Monoarthritis - Meltem Alkan Melikoğlu (Archives of Rheumatology, 2007)
Monoarthritis is among the common complaints encountered clinically and because of many possible causes the diagnosis can be difficult even for an experienced physician. An accurate differential diagnosis of monoarthritis depends on a good history and physical examination that are supplemented by the appropriate investigations. The physician must verify that the patient has arthritis, as manifested by joint swelling, and that the arthritis is limited to a single joint. Determining whether the arthritis is inflammatory or mechanical in nature and whether the disease is acute or chronic will then help the physician arrive at a presumptive diagnosis. Diagnostic investigations should include joint aspiration of synovial fluid and radiographs of the joint may also be required. A radio-nuclide scan, computed tomography or magnetic resonance imaging can be helpful in diagnosis. Treatment is based on the underlying diagnosis, but antibiotherapy is sometimes required until septic arthritis is excluded. (Rheumatism 2007; 22: 137-43)